2010
DOI: 10.1080/1533256x.2010.500970
|View full text |Cite
|
Sign up to set email alerts
|

Social Support: A Mixed Blessing for Women in Substance Abuse Treatment

Abstract: Using a personal social network framework, this qualitative study sought to understand how women in substance abuse treatment describe their network members' supportive and unsupportive behaviors related to recovery. Eighty-six women were interviewed from residential and outpatient substance abuse treatment programs. Positive and negative aspects of women's social networks were assessed via open-ended questions. Analysis was guided by grounded theory techniques using three coders. The findings extend classic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 60 publications
1
56
0
2
Order By: Relevance
“…While dominant theories describe support as advantageous, others suggest it may be provided when unwanted or unnecessary, and construed as unhelpful, inadequate, fostering dependency, and a mixed blessing (Gleason et al, 2008;Helgeson, 2003;Pal et al, 2005;Shinn et al, 1984;Tracy et al, 2010). Others posit that specific acts of support are unimportant relative to the sense of embeddedness derived from being part of a network of mutual obligation (Clark and Mills, 1979;Rook, 1990).…”
Section: Introductionmentioning
confidence: 92%
“…While dominant theories describe support as advantageous, others suggest it may be provided when unwanted or unnecessary, and construed as unhelpful, inadequate, fostering dependency, and a mixed blessing (Gleason et al, 2008;Helgeson, 2003;Pal et al, 2005;Shinn et al, 1984;Tracy et al, 2010). Others posit that specific acts of support are unimportant relative to the sense of embeddedness derived from being part of a network of mutual obligation (Clark and Mills, 1979;Rook, 1990).…”
Section: Introductionmentioning
confidence: 92%
“…As previously mentioned, a number of studies have shown a significant association between not only social support, but also social network characteristics (e.g., size, composition, density) and treatment outcomes among those with alcohol use disorders (Moos & Moos, 2007). Specifically, there is some evidence that social networks that include substance-using peers may have a negative impact and enable heavy substance use in the absence of intervention (Tracy et al, 2010;Weisner et al, 2003). Moreover, social networks that are populated by family and friends that may often unintentionally provide support that is perceived as overprotective, critical, or unwanted may undermine efforts to reduce drinking (O'Farrell et al, 1998;Rook, 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Last, our measure of social support, which primarily captured perceived emotional support, did not allow us to examine factors such as social network composition, drinking behaviors of network members, negative interactions with supportive others, and alcohol-specific support. Each of these factors has been shown to relate to drinking outcomes in previous work and may shed greater light on the mechanisms linking social environmental factors and outcomes among heavy drinkers (Longabaugh et al, 2010;Tracy et al, 2010;Zywiak et al, 2002). Despite these limitations, the findings of the current study, although tentative, may inform subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…While for people with alcohol problems, being part of a pro-alcohol, social network and denial may delay treatment seeking (Giles, 2008). The availability of social support from family and friends can influence the careers of substance users by improving confidence and motivation (Tracy, Munson, Peterson, & Floersch, 2010). However, such associates can also prevent recovery (Falkin & Strauss, 2003;Warren, Stein, & Grella, 2007).…”
Section: Introductionmentioning
confidence: 99%